2016
DOI: 10.3329/bjar.v41i2.28236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilizer on coriander seed production

Abstract: A field experiment on coriander (Coriandrum sativum L.) was carried out during rabi seasons of 2011-12 and 2012-13 in Low Ganges River Flood Plain Soil under AEZ-12 at Farming System Research and Development Site, Hatgobindapur, Faridpur to find out optimum and economic doses of fertilizers for coriander (var. BARI Dhania 1) for sustainable higher yield and to update balanced fertilizer recommendation for target yield. The experiment was laid out in a randomized complete block design with 8 treatments viz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Furthermore, anise plants treated with 20 m 3 compost + 2 kg phosphorein + 2 kg nitrobein and chemical fertilization (N 100 P 75 K 50 ) produced the highest values in volatile oil yield production (volatile oil yield per plant and per feddan) compared to the others types of fertilizers under study in 1 st and 2 nd seasons, respectively. These results are in accordance with those pointed out that coriander seed was higher when the full amount of the chemical fertilizer rate was applied, however the yield and volatile oil content were lower when just 25% of the fertilizer was used [15]. When stevia plants were fertilized with 100% of the recommended rate of NPK fertilization, the highest value was found for each of the total dry herb yield/plant as well as the dry yield of leaves and herb/feddan.…”
Section: Yield Components and Volatile Oil Productionsupporting
confidence: 91%
“…Furthermore, anise plants treated with 20 m 3 compost + 2 kg phosphorein + 2 kg nitrobein and chemical fertilization (N 100 P 75 K 50 ) produced the highest values in volatile oil yield production (volatile oil yield per plant and per feddan) compared to the others types of fertilizers under study in 1 st and 2 nd seasons, respectively. These results are in accordance with those pointed out that coriander seed was higher when the full amount of the chemical fertilizer rate was applied, however the yield and volatile oil content were lower when just 25% of the fertilizer was used [15]. When stevia plants were fertilized with 100% of the recommended rate of NPK fertilization, the highest value was found for each of the total dry herb yield/plant as well as the dry yield of leaves and herb/feddan.…”
Section: Yield Components and Volatile Oil Productionsupporting
confidence: 91%
“…Coriander ( Coriandrum sativum L.) is an annual herb belonging to the Apiaceae family and showing a global production of around 500,000 tons/year, which further results in about 500,000 tons/year of readily available coriander straw [ 31 , 32 ]. Coriander fruits are marked by the presence of both an essential oil fraction, typically representing less than 1% of the dry fruit weight, and a vegetable oil fraction of 20–28% of the dry fruit weight [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment T 3 exhibited the highest 1000-seed weight (5.25 g) and seed yield (1.70 t ha -1 ). Kamrozzaman et al (2016) also .recorded the maximum seed yield of coriander due to combined application of 2.2 kg Zn and 0.8 kg B ha -1 . Bepari et al (2018) reported that application of 45 kg S ha -1 combined with 6 kg Zn ha -1 gave the maximum growth, seed yield and quality of coriander.…”
Section: Effects Of Zinc and Boron On Seed Yield Of Coriandermentioning
confidence: 82%